Evolution of handling web applications up to the current DevOps tool - Rodríguez, Christian Adrián; Molinari, Lía Hebe; Tinetti, Fernando Gustavo (2017)
In this paper, we show the way in which many standard web applications have evolved. Most of them started with a complete independence among software development and its architecture, deployment and infrastructure design. Now, the current usage of DevOps (for Development and Operations) emerging tools are used in the context of new methodologies. We use a specific application and its own evolution as an example. Most of the development cycle, application architecture, and environments for development, testing, and QA (Quality Assurance) has changed in the last years. From 2006 to date, we have taken advantage of many new technologies as soon as they were available, each one providing some aid to (some) web development task. We also define a preliminary characterization for web applications evolution in order to analyze pros and cons of the current DevOps methodologies.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Conference on Computational Science and Computational Intelligence (CSCI) (4ta : 2017 : Las Vegas, Estados Unidos)
Keywords: APLICACIONES WEB; HERRAMIENTAS DE SOFTWARE